2007
DOI: 10.1038/sj.jid.5700900
|View full text |Cite
|
Sign up to set email alerts
|

Impaired PI3K/Akt Activation-Mediated NF-κB Inactivation Under Elevated TNF-α Is More Vulnerable to Apoptosis in Vitiliginous Keratinocytes

Abstract: Levels of the cytokines IL-6, IL-1alpha, and tumor necrosis factor-alpha (TNF-alpha) are significantly higher in lesional than in non-lesional skin of patients with vitiligo. However, how cytokines affect pigmentation is not fully understood. To examine the mechanism, Western blot analysis with TNF-alpha, Fas ligand (FasL), and downstream signaling molecules such as I-kappaB, NF-kappaB, TNF-R1-associated factor 2, Akt, and PTEN (phosphatase and tension homologue) were performed for the suction-blistered depigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 20 publications
3
52
0
Order By: Relevance
“…This finding is in agreement with a recent report [46] describing significantly higher levels of TNF-alpha and FasL in the depigmented epidermis, which indicates a role for these factors in increasing apoptosis. In this study, PTEN (phosphatase and tension homologue), which could inhibit the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) signalling pathway was significantly higher in the depigmented epidermis, implying that vitiliginous keratinocytes may be more susceptible to TNF-alphamediated apoptosis through impaired Akt and NF-kB activation.…”
Section: Discussionsupporting
confidence: 95%
“…This finding is in agreement with a recent report [46] describing significantly higher levels of TNF-alpha and FasL in the depigmented epidermis, which indicates a role for these factors in increasing apoptosis. In this study, PTEN (phosphatase and tension homologue), which could inhibit the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) signalling pathway was significantly higher in the depigmented epidermis, implying that vitiliginous keratinocytes may be more susceptible to TNF-alphamediated apoptosis through impaired Akt and NF-kB activation.…”
Section: Discussionsupporting
confidence: 95%
“…Therefore, it is logical that the above pathways are commonly involved in IL-31 and IL-33-induced effects on eosinophils cultured with dermal fibroblasts in the present study. Moreover, our findings on signaling mechanism in fibroblasts concurred with some previous studies that showed the involvement of PI3K-Akt, MAPKs and NF-κB pathways in regulating cytokine and chemokine release from keratinocytes [49][51].…”
Section: Discussionsupporting
confidence: 91%
“…However, the mechanism through which cytokines affect pigmentation and dendrites is not fully understood56 and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%